Antimicrobial Resistance A One Health Perspective - Mareș, Mihai; Hua Erin Lim, Swee; Lai, Kok-Song; Cristina, Romeo-Teodor (IntechOpen, 2021)
Tackling the realities of the antimicrobial resistance (AMR) situation today is no longer uncommon. Many battles have been fought in the past since the discovery of antibiotics between man and microbes. In the tussle of new antibiotic modifications, the transmission of resistant genes, both vertically and horizontally unveils yet another resistant attribute for the microbe, for it only to be faced with a more powerful, wide spectrum antibiotic; the cycle continues-and the winner is yet to be known. This book aims to provide some insight into various molecular mechanisms, agricultural mitigation methods, and the One Health applications to maybe, just maybe, tip the scales towards us.